[Deep-water Onuphidae (Polychaeta) from the collections of the 16th Cruise of the R/V Dmitry Mendeleev (to the generic classification of the family Onuphidae] (In Russian) - Kucheruk, N. V. (Trudy Instituta Okeanologia, Okeanologii im P. P. Shirshova, Akademia nauk SSSR, 1978)
The generic classification of family Onuphidae is discussed. Three new genera are described: Notonuphis, Aponuphis and Neonuphis. The genus Leptoecia is reestablished. The genus Paranorthia is considered as a synonym of Rhamphobrachium and Paradiopatra; the genus Paraonuphis - as a synonym of Hyalinoecia and Parhyalinoecia. The systematic postion and geographical distribution of Onuphidae is discussed. All species are distributed along the continental slope and along the underwater ridges pen?? in the oceanic eutrophical zone. Such type of geographical distribution is named here as "deep-water off slope" distribution.
World Polychaeta Database (WPolyD). Article not known to be online except at WoRMS